Are disability-related social security benefits modified by demographic, social and area-level factors? - O'Reilly, Dermot; Rosato, Michael; Maguire, Aideen (International Journal of Population Data Science, 2018)
Background In the UK Disability Living Allowance (DLA) provides non means-tested contribution towards the disability-related costs of living for disabled people. Although eligibility is based on mobility/personal care needs, other factors may be important. Methodology Three 2011 census-based measures of self-reported health (number of chronic disabilities; activity limitation (a little; a lot); and chronic poor mental health) were linked to 2011 DLA records for people aged <65. Census returns provided individual demographic, socio-economic, social and area-level characteristics. Overall, 92.5% of DLA records were matched to 1.4 million Census records. Interim Results Analyses confirms health as the main determinant of DLA Claims uptake, but that for a given level of health uptake was: higher amongst non-married and those of lower socioeconomic status ( OR 1.76; (95%CI 1.68, 1.84) most deprived vs. least deprived), lower amongst ethnic minorities (OR 0.87 (95%CIs 0.78, 0.97) non-white vs. white), migrants (OR 0.37; (95%CI 0.34, 0.39) migrants vs. non migrants) and slightly lower in rural communities (OR 0.95; (95%CI 0.93, 0.97) rural vs. urban). Conclusions Poor health is the predominant determinant of disability benefits but other social and socioeconomic factors are influential. Results of these analyses might assist in enabling resources to be targeted appropriately.